Apparent power control in single-phase grids using SCES devices: An IDA-PBC approach (2018)
This paper proposes a passivity-based control (PBC) applied to a supercapacitor energy storage system (SCES) with a single-phase pulse-width-modulated voltage source converter (VSC). The proposed strategy allows to control the interchange of active and reactive power between SCES and the distribution network using its natural reference frame. It also guarantees closed-loop stability in the sense of Lyapunov via a Hamiltonian formulation. Simulation results demonstrate the efficiency and robustness of the proposed control applied on a low-voltage single-phase distribution network under different operative conditions. © 2018 IEEE.